Effect of Surfactant Type Modifications, Glucose Inducer Concentrations, and Mineral Sources towards Lipase Enzyme Activity of Aspergillus niger ITBCC L74 on Rice Bran Substrate - Ajeng Ardani; Shinta Rismayanti; Hamid Abdillah (Nusantara Science and Technology Proceedings, 2021)
A surface-active agent is a substance added to a liquid to increase its spreading properties by lowering the surface tension. On the other hand, an inducer is a substance to triggers the production of lipase enzymes from bacteria. This study aims to formulate the microbial growth medium to produce high activity of lipase through modification of surfactant type, glucose inducer concentrations, and mineral sources using Aspergillus niger as a microbial starter and rice bran as substrate. A solid fermentation was built and prepared in this study for lipase production. The titrimetric method using NaOH solution was used to determine mol of free fatty acids per minute, type of surfactant, the optimal glucose concentration, and mineral sources on lipase enzyme activity. Tween 80 and Tween 20 are lipid-based surfactants used in this experiment. The best type of surfactant was Tween 80 with 1% of glucose inducer. It produced a lipase activity of 2.53 U/mL. In contrast, Tween 20 with 0.75% glucose inducer produced a lipase activity of 2.27 U/mL. FeSO4 and CaCl2 were the inorganic mineral sources used in this study. The best result was found at 0.6% of FeSO4, it can generate enzyme activity of 2.13 U/mL.